2022
DOI: 10.3389/fmed.2022.904414
|View full text |Cite
|
Sign up to set email alerts
|

The impact and role of hepatic hydrothorax in the prognosis of patients with decompensated cirrhosis: A retrospective propensity score-matched study

Abstract: Background and aimsHepatic Hydrothorax (HH) is one of the complications in patients with decompensated cirrhosis and its impact and role in the prognosis of patients with decompensated cirrhosis are not yet clear. Thus, this study aimed to determine the role of HH in patients with decompensated cirrhosis and the long-term impact on their mortality.Materials and methodsA retrospective study analyzed 624 patients with ascites without pleural effusion in decompensated cirrhosis and 113 patients with HH. Propensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Another retrospective study of 100 patients with hepatic hydrothorax showed 30-day and 6-month mortality rates of 19 and 32%, respectively [17]. Comparison of patients with hepatic hydrothorax to a propensity score-matched cohorts of patients with cirrhosis but without hepatic hydrothorax showed that hepatic hydrothorax is an independent risk factor for survival in patients with decompensated cirrhosis [17,18]. Our findings are in line with these previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Another retrospective study of 100 patients with hepatic hydrothorax showed 30-day and 6-month mortality rates of 19 and 32%, respectively [17]. Comparison of patients with hepatic hydrothorax to a propensity score-matched cohorts of patients with cirrhosis but without hepatic hydrothorax showed that hepatic hydrothorax is an independent risk factor for survival in patients with decompensated cirrhosis [17,18]. Our findings are in line with these previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…The occurrence of HH has been reported in 4-16% of patients with cirrhosis. Most patients with HH have ascites in combination, of which 59-85% are right-sided, 12-17% are left-sided, and 2-29% are bilateral (1,(3)(4)(5)(6)(7). There were very few reported cases of HH without ascites (8,9).…”
Section: Introductionmentioning
confidence: 99%